Keduk Beji Tradition: The Roots of Implementing Deep Ecology Environmental Ethics in Tawun Village - Rufianjani, Esavalin Oktavia; Rizal, Maulfi Syaiful (Program Studi Sastra Jawa, Fakultas Bahasa dan Seni, Universitas Negeri Semarang, 2025)
To preserve the environment and culture, the people of Tawun Village in Ngawi Regency routinely carry out the Keduk Beji tradition once a year. This tradition is an annual ritual to clean Sendang Tawun, which aims to maintain ecological balance and prevent the emergence of disasters or plagues. The routine of the Tawun community in carrying out this tradition is based on the oral tradition of “the legend of Sendang Tawun” regarding the origin of Tawun Village. The existence of a tradition that is closely related to the environment has a significant impact on the ecological balance in Tawun Village. This study aims to (1) describe the correlation between Keduk Beji tradition and the legend of Sendang Tawun, (2) describe the procession of the Keduk Beji tradition, and (3) describe the implementation of deep ecology environmental ethics in the Keduk Beji tradition. This research is qualitative research with the object of study being the Keduk Beji oral tradition carried out in Tawun Village, Ngawi Regency. The method used in this study is ethnography, which provides a comprehensive understanding of the impact of implementing the Keduk Beji tradition. Data collection techniques are done through interviews, observations, and documentation studies. The study results show that the Tawun community applies environmental ethics (principles of deep ecology), which are guided by the values ​​inherited from their ancestors. This study distinguishes between empirical reality in the form of cultural practices of the community in the Keduk Beji tradition and ideal values contained in the principles of deep ecology as a reference in environmental conservation.